Review of Autonomous Space Robotic Manipulators for On-Orbit Servicing and Active Debris Removal - Nasim Fallahiarezoodar; Zheng H. Zhu (Space: Science & Technology, 2025)
The increasing demand for on-orbit servicing (OOS) tasks, such as satellite repair, space debris removal, refueling, and upgrades, has driven the need for advanced robotic systems capable of autonomous and precise operations in space. At the core of these tasks are unmanned spacecraft equipped with robotic manipulators designed to execute critical capture and manipulation maneuvers. This paper presents a comprehensive review of space robotic missions and methodologies for effective OOS and space debris removal. It examines control strategies applied across different phases of these missions, with a focus on their implementation in 2 operational modes: free-floating and free-flying. Detailed discussions are provided on methodologies for the pre-capture phase, covering both motion planning and vision-based estimation. For the post-capture phase, the paper explores control methods designed to stabilize captured targets. Additionally, it investigates ground verification experiments, which are crucial for validating the performance of space robots under microgravity-like conditions. These experiments yield valuable insights into the dynamic behavior of space robotic systems and play an important role in advancing space robotics research. By consolidating recent advancements and identifying key technological gaps, this review highlights future research directions aimed at improving the reliability, adaptability, and safety of robotic manipulators in addressing the challenges of OOS and space debris removal.